The Role of Some Selected Notable Northern Nigerian First Ladies Towards Human Development and Woman Emancipation in Nigeria - Saidu, Amina Ramat; Saleh, Saleh Andy (NIU Journal of Humanities, 2023)
This study analysed the activities of some selected prominent first ladies in northern Nigeria and how they impacted on the lives of the needy within the societies around them and beyond.  The paper focused on the activities of their pet projects which served as a means of providing development projects through fund raising from public and private institutions.  The funds realised was geared towards human development and capacity building to empower the communities and societies around them.  The paper analysed both primary and secondary sources of data in order to extract reliable information for the purpose of this study.  Through the exercise of their influence, First Ladies have been able to establish pet projects with funds raised from public institutions, corporate organisations and international donor agencies.  In the light of this, the paper studies the efforts of first Ladies which have contributed significantly to human development index of the target group and has provided strategic platform for women mobilization and consciousness in public affairs.